The jeans encyclopedia :
Presented in an easy-to-access A to Z format, traces the evolution of jeanswear's heritage, including profiles of existing and once-famous brands, leading companies and well-known personalities, historical facts, bestselling styles, fabric developments, technical definitions and more.